Perception of the climate risk phenomena in Suceava municipality and surrounding areas - Dumitru MIHĂILĂ; Mădălina - Naomi JIBU; Petruț-Ionel BISTRICEAN; Vasilică- Dănuț HORODNIC; Mihaela ȚICULEANU (CIURLICĂ) (Present Environment and Sustainable Development, 2022)
This study is the first to date which addresses the issue of public perception of meteorological and climate risks in the city of Suceava and surrounding areas and among the few studies on this topic conducted at the national level. The aim of the study is to explore from several perspectives the impact of severe atmospheric phenomena on the social and economic environment of Suceava and its surroundings, but also the way in which the population relates to them. The study is based on an online survey (January 2021) regarding the meteorological-climate risk phenomena that occur in Suceava and the neighboring localities respectively, which was applied to a number of 514 inhabitants who have permanent or temporary residence in this area. The survey contains 29 items; of these, one item required additional clarification, which was obtained by asking a complex question to an additional number of 253 respondents (May-June 2021). The respondents belonged to several age groups and socio-professional categories. Based on the received answers, we constructed a complex picture of the way in which the population of Suceava and the neighboring suburban localities relate to these dangerous phenomena, which can be useful both scientifically and in practice by the authorities. We found that the population of Suceava is familiar at an average to good level with the issue of meteorological-climatic risks.